Wind power for the world : the rise of modern wind energy - Maegaard, Preben; Krenz, Anna; Palz, W. (Wolfgang), 1937- (Pan Stanford series on renewable energy ;, 2013)
This book sheds light on how the modern 3-bladed wind turbine came into being, and who, how and what in the proceeding period caused the success. It looks back over three decades to find the roots of this exciting development, a long cavalcade of developers, inventors, and manufacturers including the Danish authors who themselves were part of the breakthrough. Written for non-specialists, the book covers minimal science, emphasizing the story of how wind power became a worldwide 30-billion-euro business employing nearly one million people.